Orbit and Positioning Accuracy for New Generation Beidou Satellites during the Earth Eclipsing Period. (26th March 2018) - Li, Xiaojie; Hu, Xiaogong; Guo, Rui; Tang, Chengpan; Zhou, Shanshi; Liu, Shuai; Chen, Jianbing
Abstract : The Beidou System (BDS) started functioning at the end of 2012. The Yaw-Steering (YS) attitude mode for Inclined Geosynchronous Orbit (IGSO) and Medium Earth Orbit (MEO) satellites in BDS ensures that the solar panels face the Sun. The orbit radial accuracies for IGSO/MEO satellites are 0·5 m and the User Equivalent Range Errors (UERE) are 1·5 m in YS mode. BDS-2 satellites adopt Orbit-Normal (ON) mode to meet the power supply and thermal control requirements of the satellite during deep Earth eclipse periods. In ON mode, long-term orbit ephemeris accuracy monitoring in the Operational Control System (OCS) of BDS indicates that the orbit accuracies for IGSO/MEOs are reduced to a few hundreds of metres, seriously affecting the positioning accuracy and navigation service capability of the BDS system. Solar Radiation Pressure (SRP) is difficult to model in ON mode. Continuous Yaw-Steering (CYS) mode is available for new generation Beidou satellites launched since 2015. The orbit accuracies for these new generation Beidou (BDS-3) satellites were estimated based on BDS monitoring station data and SRP models including ECOM 9/5/3. The evaluation method consisted of four steps, namely, orbit internal consistency analysis, UERE calculation, Satellite Laser Ranging (SLR) data fitting Root Mean Square (RMS) determinations and positioning performance analysis; the data gathering period lasted for more than 60 days and included two CYS periods and one ON period. The experiments showed that the orbit accuracy of the radial component in CYS mode for the BDS-3 satellites degrades by 2 to 3 cm and positioning accuracy degrades only by 1 cm over that in YS mode which is just a small reduction in accuracy compared with the decimetre-level BDS orbit accuracy and the metre-level single point positioning accuracy with BDS pseudorange data. This overcomes declining orbit and positioning accuracy issues in ON mode for BDS-2 satellites. Other results also show that the reliability of BDS has been improved.